Comprehensive molecular characterization of pheochromocytoma and paraganglioma - Fishbein, Lauren (Cancer Cell, 2017)
We report a comprehensive molecular characterization of pheochromocytomas and paragangliomas (PCC/PGLs), a rare tumor type. Multi-platform integration revealed that PCC/PGLs are driven by diverse alterations affecting multiple genes and pathways. Pathogenic germline mutations occurred in eight PCC/PGL susceptibility genes. We identified CSDE1 as a somatically-mutated driver gene, complementing four known drivers (HRAS, RET, EPAS1, NF1). We also discovered fusion genes in PCC/PGL, involving MAML3, BRAF, NGFR and NF1. Integrated analysis classified PCC/PGLs into four molecularly-defined groups: a kinase signaling subtype, a pseudohypoxia subtype, a Wnt-altered subtype, driven by MAML3 and CSDE1, and a cortical admixture subtype. Correlates of metastatic PCC/PGL included the MAML3 fusion gene. This integrated molecular characterization provides a comprehensive foundation for developing PCC/PGL precision medicine.